Development of an innovative temperature control system in a fermenter: application to the case of the wine industry. Issue 1 (1st April 2022) - Malavasi, Matteo; Cattani, Luca; Bozzoli, Fabio; Rainieri, Sara
Abstract: Temperature is one of the most important parameters influencing the fermentation in wine making process. Indeed, its control during this phase is fundamental to obtain a high-quality product. Fermentation is an exothermic process and for this reason a good cooling system in fermenter tanks is required. The temperature control systems usually adopted are represented by an external cooling jacket in which cold water flows. This system is based on the water circulation which is activated only when a critical temperature in the fermenter is exceeded making the control less precise. In this paper an alternative solution based on heat pipe technology is designed and its feasibility is investigated through the application of its ideal variant. This innovative temperature control system has the advantage to work on continuous mode, thus keeping the temperature in the fermenter more uniform during the whole process. Moreover, the proposed system is fully passive reducing the costs of this process phase. The results of this work demonstrated that the device application could be feasible and that it represents a promising solution.